REDESIGN APLIKASI GRAVOTE DENGAN METODE DESIGN THINKING - Anissa Edriani Zahra (2021)
Voting is one method to take a joint decision through a vote. However, in real life there are still many shortcomings in the implementation of the vote in Indonesia, including in the scope of UPN Veteran Jakarta. One of the reason is because of the conventional method of voting so that it gives space for possible errors in the calculation of votes. This may result in a decision that is not guaranteed validity. An android-based online voting app called "Gravote" designed to overcome the shortcomings and problems that occur on the ballot manually. Gravote is an online voting application intended for student organizations at UPN Veteran Jakarta. However, the features in gravote application have not met the needs of the user optimally. A reassessation is needed to find out what the needs of student organizations related to voting activities, either by change or addition of features. Therefore, a redesign was carried out using the Design Thinking method so that Gravote can be used according to the needs of its users.